2020
DOI: 10.18662/rrem/12.3/307
|View full text |Cite
|
Sign up to set email alerts
|

Developing Healthcare Competency in Future Teachers

Abstract: The progressive mankind has realized that medicine has only relative possibilities in the elimination of the results of destructive processes in the human body and mind, whereas preventive measures, propaedeutics, physical education and sport and other forms which eliminate causes rather than effects are more effective. Experimental work aims to verify the effectiveness of pedagogical conditions, which assure the process of developing healthcare competency in future teachers. The research is based on a hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 8 publications
1
50
0
Order By: Relevance
“…The results of the study confirm (Badalyan et al, 1988;Kozyavkin et al, 1999;Semenova, 2007) that movement disorders in children with cerebral palsy are a kind of deviation of motor development, without appropriate correction affects the formation of neuropsychic functions of the child. Information has been confirmed that the success of the application of physical rehabilitation measures depends on the timing of application, the appropriateness of the selection of funds, the observance of the principles of physical education (Efimenko & Sermeev, 1991) and should be of a complex nature (Voronin, & Trach, 2008).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The results of the study confirm (Badalyan et al, 1988;Kozyavkin et al, 1999;Semenova, 2007) that movement disorders in children with cerebral palsy are a kind of deviation of motor development, without appropriate correction affects the formation of neuropsychic functions of the child. Information has been confirmed that the success of the application of physical rehabilitation measures depends on the timing of application, the appropriateness of the selection of funds, the observance of the principles of physical education (Efimenko & Sermeev, 1991) and should be of a complex nature (Voronin, & Trach, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…The study scheme is as follows: the indicators of basic motor functions assessment (IBMFA) were measured before, after 6 months and after the experiment, since the development of motor skills is slow and very difficult, due to the immaturity of nervous processes and the influence of tonic muscle reactions, which is confirmed by many years of scientific practice (Kozyavkin, Shestopalova, & Podkorytov, 1999;Mastyukova, 1991) determination of indicators of joint mobility, muscle tone and strength, speed of hand reaction and manipulative activity was carried out before, after 4 months, after 8 months and after a one-year course of rehabilitation to track the dynamics of development of indicators of the functional state of the musculoskeletal system; assessments of the influence of hydrokinesis therapy on the social-emotional state and activity of playing activity were determined before and after rehabilitation, since the main task of the work is to overcome tonic muscular reactions, pathological attitudes and, on this basis, to form step-by-step motor skills.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations